Benefits of fostering emotional intelligence in the inclusive curriculum and why assess it: a systematic review - Jiménez-Vázquez, David; Soriano-Sánchez, José-Gabriel; Parras-Blanca, Eva-María (Revista Innova Educación, 2023)
In adolescence the personality and social adjustment of the individual emerges, where health is determined by psychological, physical, biological and social factors. In this sense, emotional intelligence is a psychological construct that improves the quality of life of the individual. Therefore, the aim of this study was to identify the importance of EI in the educational, inclusive and innovative curriculum during adolescence, as well as its relationship with different psychological variables, presenting the most characteristic instruments for its measurement and evaluation. Consequently, a search for articles was carried out in different databases, such as PsycINFO, Scopus and Web of Science. Thus, a total of 687 documents were obtained which, after applying the inclusion criteria, left 33 studies for review. The results made up a sample size of 32,228 adolescents between 10 and 19 years of age, which revealed the importance of emotional intelligence in the well-being and improvement of the quality of life of adolescents. In conclusion, it is considered that education professionals should take into account the results of this work, so as to promote the development of emotional intelligence in the inclusive curriculum, in order to ensure the empowerment and quality of life of students
Keywords: adolescents; well-being; emotional intelligence; innovation; systematic review